Ш.СЕЙИТОВТЫҢ «ХАЛҚАБАД» РОМАНЫ ТИЛИНДЕ РӘЎИШ ФРАЗЕОЛОГИЗМЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Юсупова, Б.Т. (FAN va JAMIYAT, 2020)
The article is devoted to the study of using phraseologisms expressed by adverbs in the novel «Khalkabad» by the famous Karakalpak writer Sh.Seyitov.